The Urgency of Legal Protection to the Trademarks in the Global Era - Anis Mashdurohatun; Gunarto Gunarto; Lathifah Hanim (UNISSULA, 2018)
Globalization is nothing but capitalism in its most recent form. Strong and rich countries practically control the world economy and smaller countries are increasingly powerless because they are unable to compete through Intellectual Property Protection including trademarks. The purpose of this research is to examine and to analyze the role of the State in providing legal protection Against trademarks, and factors that influence and formulate their legal protection policies. The approach method in this research is empirical juridical. The data used were primary and secondary data. The results of the research were analyzed analytical descriptively. The results of the study found that the role of the State in providing legal protection for trademarks of business people was not optimal, this was due to several factors including the low understanding of the importance of trademark intellectual property rights protection for businesses and society as consumers. Government policies globally through the Asean Economic Community Blueprint, which contains four main pillars, including the economic competitiveness of Intellectual Property Rights integrated with the global economy.